Genetic erosion over time of rice landrace agrobiodiversity - Ford-Lloyd, Brian V.; Brar, Darshan; Khush, Gurdev S.; Jackson, Michael T.; Virk, Parminder S. (Cambridge University Press, 2009)
Changes in global biodiversity at the genetic level have proved difficult to determine for most organisms because of lack of standardized, repeated or historical data; this hampers the attempts to meet the convention on biological diversity (CBD) 2010 targets of reducing loss of genetic diversity, particularly of crop species. For rice, where germplasm and genetic data have been collected throughout South and Southeast Asia over many decades, contrary to popular opinion, we have been unable to detect a significant reduction of available genetic diversity in our study material. This absence of a decline may be viewed positively; over the 33-year timescale of our study, genetic diversity amongst landraces grown in traditional agricultural systems was still sufficiently abundant to be collected forex situconservation. However, if significant genetic erosion does take place in the future as a result of accelerating global warming and/or major changes in land use or agricultural practices, will it be catastrophic or gradual, and how will it be detected? We have shown a strong link between numbers of landraces collected (and therefore extant) and genetic diversity; hence, we have a clear indicator to detect loss of genetic diversity in the future. Our findings lend considerable support forex situconservation of germplasm; the more than substantial genetic resources already in genebanks are now safe. On the other hand, it is the germplasm growing in farmers' fields, continually adapting genetically to changing environmental conditions and evolving novel genetic forms, whose future has been much less certain but can now be effectively monitored using our criteria.